Central bank independence and accountability: a literature review - Bandura, Romina (Archīum Ateneo, 2006)
The tension between policy decisions taken by technocrats versus those responsive to the popular will is present in many areas of economic policy. This tension is particularly present in the discussion of institutional arrangements for central banks, specifically on central bank independence. The following note reviews the main issues discussed in the academic literature on central bank independence to illustrate and understand this tension in a narrower dimension, ie monetary policy. In the academic literature, governments that are unable to make credible promises are regarded to be hindering economic development and effective policymaking. Political systems characterized by checks and balances and the delegation of authority to independent agencies (such as an independent central bank) have been promoted as an institutional solution to this problem (Keefer and Stasavage 2003). We have seen an increase in countries adopting this approach in recent years, with most of the industrial countries and many developing countries having highly independent central banks (Mishkin 2006; Maxfield, 1997, Arnone, Laurens and Segalotto 2006b, Pollillo and Guillén 2005, Wessels 2006)